2022
DOI: 10.1002/jimd.12483
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestation and long‐term outcome of citrin deficiency: Report from a nationwide study in Japan

Abstract: Citrin deficiency is an autosomal recessive disorder caused by mutations in the SLC25A13 gene. The disease can present with age‐dependent clinical manifestations: neonatal intrahepatic cholestasis by citrin deficiency (NICCD), failure to thrive, and dyslipidemia by citrin deficiency (FTTDCD), and adult‐onset type II citrullinemia (CTLN2). As a nationwide study to investigate the clinical manifestations, medical therapy, and long‐term outcome in Japanese patients with citrin deficiency, we collected clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 52 publications
0
26
1
Order By: Relevance
“…The results of our study suggested that the carrier rates of c.1803C > G may be frequent in the central cities of China, and there are differences in the distribution of the mutation spectrum in different geographical areas. As for the relationship between genotype and phenotype, although some studies declared that there were likely to be phenotype–genotype correlations in the specific genotypes ( 11 ), in our study, no obvious genotype-phenotype relationship seems to be found. For example, heterozygous genotypes including c.1803C > G were found in patient 1 and 2, but their birth weight, AST, Fib, PA and prothrombin time have a marked difference.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The results of our study suggested that the carrier rates of c.1803C > G may be frequent in the central cities of China, and there are differences in the distribution of the mutation spectrum in different geographical areas. As for the relationship between genotype and phenotype, although some studies declared that there were likely to be phenotype–genotype correlations in the specific genotypes ( 11 ), in our study, no obvious genotype-phenotype relationship seems to be found. For example, heterozygous genotypes including c.1803C > G were found in patient 1 and 2, but their birth weight, AST, Fib, PA and prothrombin time have a marked difference.…”
Section: Discussioncontrasting
confidence: 76%
“…can manifest as jaundice, elevated liver enzyme, hepatosplenomegaly, and growth retardation. Meanwhile, other inherited metabolic diseases(such as galactosemia (6), hepatocerebral mitochondrial DNA depletion syndrome (7-9), arginylsuccinuria (10), etc.) can also have symptoms similar to NICCD.…”
Section: Discussionmentioning
confidence: 99%
“…According to Yed, mutation I, III, and X, but not II, play major roles in Taiwanese infants with NICCD [30], while mutation II was the most common mutation SLC25A13 in Japan [17,30]. A recent study in Japan as a nationwide scale with 222 CD patients showed that only 2 variants c.1177 + 1G>A (mut II) and c.1638_1660dup (mut III) overlapped with our 12 defined variants, with a much higher frequency of 34% vs. 0.56% and 3% vs. 0.75%, respectively [33]. Overall, the results of this study revealed that almost all participants (99.7%) carrying at least one of these four mutations, with 84.59% patients carrying homozygous genotype of mut I/I and 14.38% patients carrying compound heterozygous of mut I.…”
Section: Discussion Mutation Identification and Genotypementioning
confidence: 60%
“…Current treatments for CD are low-carbohydrate and high-protein/−fat diets, which are based in the unique food preferences of patients, and sodium pyruvate or medium chain triglycerides supplementation [ 15 ]. In the more severe cases, patients can suffer liver failure and the only therapeutic option is liver transplantation [ 10 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is of special consideration in the case of non-sense mutations leading to no protein expression, either due to a premature stop codon or instability of the protein. Interestingly, the more prevalent mutations in CD fall in that categories and patients show no protein expression [ 16 , [23] , [24] , [25] ]. It is not known whether the immune system of the patient may react to the recombinant gene product [ 20 , 21 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%